Drip fertigation significantly reduces nitrogen leaching in solar greenhouse vegetable production system. (February 2019) - Lv, Haofeng; Lin, Shan; Wang, Yafang; Lian, Xiaojuan; Zhao, Yiming; Li, Yingjie; Du, Jiuyue; Wang, Zhengxiang; Wang, Jingguo; Butterbach-Bahl, Klaus
Abstract: Vegetable production in solar greenhouses in northern China results in the excessive use of nitrogen (N) fertilizers and water via flooding irrigation. Both factors result in low N use efficiency and high environmental costs because groundwater becomes contaminated with nitrate (NO3 − ). Four consecutive tomato ( Lycopersicum esculentum Mill.) cropping seasons were tested whether drip fertigation and/or the incorporation of maize straw (S) may significantly reduce NO3 − and dissolved organic N (DON) leaching while increasing the water-use efficiency (WUE) and partial factor productivity of applied N (PFPN ) of the tomatoes. The following treatments were used: ① conventional flooding irrigation with overfertilization (CIF, 900 kg N ha −1 season −1 ), ② CIF + S, ③ drip irrigation with optimized fertilization (DIF, 400 kg N ha −1 season −1 ), ④ DIF + S. We found that (1) DIF significantly increases the PFPN and WUE by 262% and 73% without compromising the yield compared with CIF, respectively. (2) For CIF, approximately 50% of the total N input was leached at a NO3 − /DON ratio of approximately 2:1. (3) Compared with CIF, DIF reduced NO3 − and DON leaching by 88% and 90%, respectively. Water percolation was positively correlated with N leaching ( p < 0.001). (4) Straw application only reduced NO3 − leaching losses in the first year and did not affect DON leaching overall, although DON leaching was increased in DIF in the first growing season. In conclusion, DIF significantly reduces NO3 − and DON leaching losses by approximately 90% compared with the current farmer practice (CIF). Considering the significant DON leaching losses, which have been overlooked because previous measurements focused on NO3 −, DON should be considered as a primary factor of environmental pollution in conventional solar greenhouse vegetable production systems. Graphical abstract: Highlights: Drip fertigation increases water and nitrogen use efficiency without yield jeopardy. For conventional flooding irrigation, 50% of total N input was leached. Dissolved organic nitrogen (DON) accounted for 1/3 of total N leaching. Drip fertigation reduced dissolved inorganic and organic N leaching by 90%. Straw addition reduced nitrate leaching in the first year, less affect DON leaching. Abstract : For CIF, 50% of total N input was leached and DON accounted for 33% of the total leached N. Drip fertigation reduced the dissolved inorganic and organic N leaching by 90% compared with CIF.